THE PROBLEMATICS OF CRIMINAL SANCTIONS RELATED TO PLASTIC SURGERY: ETHICAL AND LEGAL ISSUES - Widyastuti, Ni Luh Wiweka; Darma, I Made Wirya (Faculty of Law, Universitas Pekalongan, 2024)
Plastic surgery presents complex challenges in terms of ethics and law, including conflicts between medical principles and patients' aesthetic desires, enforcement of regulations against illegal practices, appropriate application of criminal sanctions, and the need to balance increasing demand with adequate safety standards and patient protection. This study aims to analyze the application of criminal sanctions for malpractice in plastic surgery from the perspective of medical ethics and criminal law in Indonesia, as well as to identify the challenges in formulating regulations that balance patient protection and medical freedom in the context of plastic surgery. The study employs a normative legal method with a legislative and conceptual approach, analyzing primary and secondary legal materials through a literature review, and applies descriptive qualitative analysis to understand the problems of criminal sanctions and ethical aspects in plastic surgery in Indonesia. The results indicate that the application of criminal sanctions for malpractice in plastic surgery in Indonesia involves complex considerations from the perspectives of medical ethics and criminal law. Key challenges include protecting patients from surgical risks, especially elective procedures, while respecting doctors' medical autonomy; ensuring informed consent without restricting clinical decision-making; addressing ethical dilemmas related to patient requests; integrating technological advancements without compromising safety; strengthening oversight and law enforcement against illegal practices; and protecting consumers from misleading advertisements. The application of criminal sanctions faces challenges in proving negligence, particularly due to the subjective nature of aesthetic plastic surgery. There is a need for synergy between law enforcement and ethical regulation to balance patient protection and medical freedom, ensuring justice for both patients and responsible medical practitioners